Atrial and ventricular ejection force of the fetal heart: Which of the four chambers is the dominant? - Elaheh Malakan Rad; Toktam Sheykhian; Ali Akbar Zeinaloo (Annals of Pediatric Cardiology, 2019)
Background/Aim: This study aimed to measure and compare the ejection force of the cardiac chambers in healthy singleton fetuses and to investigate the relationship of ejection force of cardiac chambers with gestational age, fetal sex, and fetal heart rate. Patients and Methods: A prospective study was performed on 68 singleton fetuses with a gestational age of 17–34 weeks. Atrial and ventricular ejection force was measured. Measurements were repeated in 18 of the fetuses to assess intraobserver reliability. Results: The right atrium had the highest ejection force of all the cardiac chambers. Ejection force of both atria and ventricles increased with gestational age. Conclusion: The right atrium is the dominant chamber of the fetal heart in 17–34 weeks of gestation. Comparison of our values with previous studies indicates that left atrial ejection force almost doubles in the 1st month after birth. This study highlights the crucial role of the right atrium in the fetal cardiac function during 17–34 weeks of gestation.